1988
DOI: 10.1007/bf01337463
|View full text |Cite
|
Sign up to set email alerts
|

A note on the coefficient of viscosity of pure molten 2,4,6-trinitrotoluene (TNT)

Abstract: The viscosity of pure molten TNT has been investigated over the temperature range 82.0°-95.4 °C. The temperature dependence of viscosity was found to be best represented by a relation of the type q = A e wT where A = 0.000541, B -= 3570, r/is the viscosity in mPa s and T is the temperature in Kelvin. Earlier work, which suggests an inverse temperature dependence of the flow activation energy, is shown to include an error in the published equation for the temperature dependence of the viscosity of molten TNT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Melt-cast explosive suspensions are solid–liquid two-phase mixtures. Generally, the liquid phase exhibits a Newtonian viscous behavior [ 3 , 42 , 43 ]. However, when the solid phase is dispersed in the liquid phase, the resultant melt-cast explosive suspensions usually exhibit a non-Newtonian (shear thinning) viscous behavior [ 6 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Melt-cast explosive suspensions are solid–liquid two-phase mixtures. Generally, the liquid phase exhibits a Newtonian viscous behavior [ 3 , 42 , 43 ]. However, when the solid phase is dispersed in the liquid phase, the resultant melt-cast explosive suspensions usually exhibit a non-Newtonian (shear thinning) viscous behavior [ 6 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…For TNT, A=2.78, B=-2810 and C=7.8 -105 . We have recently shown that these values are in error [5].…”
Section: Introductionmentioning
confidence: 96%
“…The rheological behavior of melt-cast explosives has been explored to some extent in previous work, especially for trinitrotoluene-based (TNT-based) melt-cast explosives. The general qualitative law for the rheological behavior of TNT-based melt-cast explosives can be summarized as follows: (1) Molten TNT is similar to a Newtonian fluid [1][2][3], whereas TNT-based melt-cast explosive suspensions are generally shear-thinning (non-Newtonian) fluids [4][5][6]. (2) The viscosity of the suspensions increases with increasing solid content [4,[7][8].…”
Section: Introductionmentioning
confidence: 99%